Evaluasi Kinerja Pengawas Sekolah dalam Meningkatkan Mutu Pendidikan Melalui Supervisi Akademik di TK Kabupaten Bireuen: Penelitian - Nurulhadi; Marwan; Jamaluddin Idris (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to evaluate the performance of school supervisors in improving education quality through academic supervision at kindergartens (TK) in Bireuen Regency. Supervisors play a crucial role in ensuring the quality of learning through academic and managerial supervision. This qualitative research employed a case study method at five kindergartens, involving five principals and five teachers as key informants. Data were collected through interviews, observations, and documentation, and analyzed interactively through data reduction, display, and verification. The results show that academic supervision planning has been carried out but remains administrative and lacks a needs-based school analysis. The implementation of supervision followed formal procedures, but the intensity and quality of coaching remained low, with a stronger emphasis on administration rather than teaching practice development. Follow-up plans were formulated in the form of training, mentoring, and teacher learning communities, though implementation was hindered by limited resources and coordination. This study recommends strengthening academic supervision through structured, participatory, and sustainable strategies to improve the quality of early childhood education more evenly.